БАГАНУУРЫН ОРДЫН НҮҮРСНИЙ ШИНГЭРҮҮЛЭЛТИЙН БОЛОН ШИНЖ ЧАНАРЫН СУДАЛГАА - Ариунаа, А; Цацрал, Г; Эрдэнэчимэг, Р; Пүрэвсүрэн, Б; Дугаржав, Ж (Proceedings of the Mongolian Academy of Sciences, 2016)
The chemical characteristics, pyrolysis and thermal dissolution of Bagnuur lignite coal,  which is located in the Central economic region of Mongolia were studied. The proximate, ultimate, petrographic and IR analysis results have been confirmed that the Baganuur coal is a low-rank B2 mark lignite coal. Analysis of ash composition of the sample shows Baganuur sample has lower contents of silicium, calcium, aluminum, ferric and zincium oxides. The results of pyrolysis of Baganuur coal at different heating temperatures show that a maximum yield 7.0% of liquid product can be obtained at 600°C. The results of thermal dissolution of Baganuur coal in tetralin with constant mass ratio between coal and tetralin (1:8) at 450°C show that 40% of liquid product can be obtained after thermal decomposition of the coal organic mass.